The Effect Of Retail Marketing Mix On Customer Satisfaction At PT Bumi Nyiur Swalayan In Palu City - Nuranda Deita; Wahyuningsih Wahyuningsih; Ira Nuriya Santi; Farid Farid (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
This study aims to test and analyze the effect of marketing mix consisting of product, price, location, and promotion on customer satisfaction of Bumi Nyiur Supermarket in Palu City. Data collection was carried out using a survey method through questionnaire distribution. The study population was all customers of Bumi Nyiur Supermarket in Palu City. The sampling technique used purposive sampling and the determination of sample size used roscoe's theory by setting a sample of twenty times the number of variables and obtained 100 samples. The data analysis technique used multiple linear regression. The results of the study showed; Marketing mix consisting of product, price, location, and promotion simultaneously have a positive and significant effect on customer satisfaction, promotion has a positive and significant effect on customer satisfaction, price has a positive and significant effect on customer satisfaction, location has a positive and significant effect on customer satisfaction and promotion has a positive and significant effect on customer satisfaction.